PENGARUH PEMBERIAN INSENTIF DAN PENILAIAN KINERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BODY DAN CAT AUTO2000 - Febri Ramadhani; Indah Listyani; Edy Suwasono; Helmi Agus Salim (Commodities, Journal of Economic and Business, 2022)
The problem that is the focus of this research is the problem only on human resource factors which specifically focus on giving incentives and Performance Appraisal on employee productivity so that this research is expected to not be able to expand from the determined topic. The population in this study were 27 employees who were sampled by the saturated sampling method. The data analysis technique used is validity and reliability test, and multiple linear regression test through SPSS software. Based on the analysis that has been carried out, the results of the research are obtained: (1) Partially giving incentives has a positive and significant influence on the productivity of the work of employees of the Body and Paints of Auto2000 Suharmadji Kediri. (2) Partially the performance appraisal has a positive and significant influence on the work productivity employees Body and Paints of Auto2000 Suharmadji Kediri. (3) Simultaneously giving incentives and evaluating performance has a positive and significant influence on the work productivity of employees in the Body and Paints of Auto2000 Suharmadji Kediri.